The Potential of Irvingia gabonensis: Can it contribute to the improvement of the livelihoods of producers in Southern Cameroon? - Awono, A.; Djouguep, A.; Zapfack, L.; Ndoye, O. (2009)
Non Timber Forest Product (NTFP) processing in Cameroon is still limited to traditional commerce, which mainly involves the supply of raw materials. Furthermore, lack of knowledge on the availability of NTFPs in their biotope does not allow for accurate planning to ensure sustainable management and their contribution to the fight against poverty. Based on a survey carried out in cocoa agroforests in Southern Cameroon and an evaluation of Irvingia gobonensis kernels processing chain, we argue that, on the one hand, the resource is not as abundant as is generally thought and that processing can improve incomes of households at local, national and even regional levels on the other hand. Processing of I. gabonensis kernels and consumer reactions to the derivative products are also discussed. It will also be illustrated that, with results from laboratory analyses, the further-processed products are of good quality and are safe for human consumption.